How to solve this summation ?
\sum_{0\le x_1\le x_2...\le x_n \le n}^{}\binom{k+x_1-1}{x_1}\binom{k+x_2-1}{x_2}...\binom{k+x_n-1}{x_n}
where k , n are known.
Due to hockey-stick identity ,
\sum_{i=0}^n\binom{i+k-1}{i}=\binom{n+k}{k}
Answer
Suppose we seek to evaluate
\sum_{0\le x_1\le x_2\cdots \le x_n \le n} {k+x_1-1\choose x_1} {k+x_2-1\choose x_2} \cdots {k+x_n-1\choose x_n}.
Using the Polya Enumeration Theorem and the cycle index of the
symmetric group this becomes
Z(S_n) \left(Q_0+Q_1+Q_2+\cdots +Q_n\right)
evaluated at
Q_m = {k-1+m\choose m}.
Now the OGF of the cycle index Z(S_n) of the symmetric group is
G(z) = \exp \left(a_1 \frac{z}{1} + a_2 \frac{z^2}{2} + a_3 \frac{z^3}{3} + \cdots \right).
The substituted generating function becomes
H(z) = \exp \left(\sum_{p\ge 1} \frac{z^p}{p} \sum_{m=0}^n {k-1+m\choose m}^p\right) = \exp \left(\sum_{m=0}^n \sum_{p\ge 1} \frac{z^p}{p} {k-1+m\choose m}^p\right) \\ = \exp \left(\sum_{m=0}^n \log\frac{1}{1-{k-1+m\choose m} z}\right) = \prod_{m=0}^n \frac{1}{1-{k-1+m\choose m} z}.
Some thought shows that this could have been obtained by inspection.
We use partial fractions by residues on this function which we
re-write as follows:
(-1)^{n+1} \prod_{m=0}^n {k-1+m\choose m}^{-1} \prod_{m=0}^n \frac{1}{z-1/{k-1+m\choose m}}.
Switching to residues we obtain
(-1)^{n+1} \prod_{m=0}^n {k-1+m\choose m}^{-1} \sum_{m=0}^n \frac{1}{z-1/{k-1+m\choose m}} \\ \times \prod_{p=0, \; p\ne m}^n \frac{1}{1/{k-1+m\choose m}-1/{k-1+p\choose p}}.
Preparing to extract coefficients we get
(-1)^{n} \prod_{m=0}^n {k-1+m\choose m}^{-1} \sum_{m=0}^n \frac{{k-1+m\choose m}}{1-z{k-1+m\choose m}} \\ \times \prod_{p=0, \; p\ne m}^n \frac{1}{1/{k-1+m\choose m}-1/{k-1+p\choose p}}.
Doing the coefficient extraction we obtain
(-1)^{n} \prod_{m=0}^n {k-1+m\choose m}^{-1} \sum_{m=0}^n {k-1+m\choose m}^{n+1} \\ \times \prod_{p=0, \; p\ne m}^n \frac{1}{1/{k-1+m\choose m}-1/{k-1+p\choose p}} \\ = (-1)^{n} \prod_{m=0}^n {k-1+m\choose m}^{-1} \sum_{m=0}^n {k-1+m\choose m}^{2n+1} \\ \times \prod_{p=0, \; p\ne m}^n \frac{1}{1-{k-1+m\choose m}/{k-1+p\choose p}} \\ = (-1)^{n} \sum_{m=0}^n {k-1+m\choose m}^{2n} \prod_{p=0, \; p\ne m}^n \frac{1}{{k-1+p\choose p}-{k-1+m\choose m}}.
The complexity here is good since the formula has a quadratic number
of terms in n. The number of partitions that a total enumeration
would have to consider is given by
Z(S_n) \left(Q_0+Q_1+Q_2+\cdots +Q_n\right)
evaluated at Q_0 = Q_1 = Q_2 = \cdots = Q_n = 1 which gives the
substituted generating function
A(z) = \exp\left((n+1)\log\frac{1}{1-z}\right) = \frac{1}{(1-z)^{n+1}}.
This yields for the total number of partitions
{n+n\choose n} = {2n\choose n}
which by Stirling has asymptotic
(consult OEIS A00984)
\frac{4^n}{\sqrt{\pi n}} \quad\text{and}\quad n^2\in o\left(\frac{4^n}{\sqrt{\pi n}}\right).
For example when n=24 and k=5 we would have to consider
{48\choose 24} = 32.247.603.683.100 partitions but the formula
readily yields
424283851839410438109261697709077430045882514844\\ 665327684062172306602549601581316037895634544256\\ 47212676100.
Additional exploration of these formulae may be undertaken using the
following Maple code which contrasts total enumeration and the closed
formula.
A :=
proc(n, k)
option remember;
local iter;
iter :=
proc(l)
if nops(l) = 0 then
add(iter([q]), q=0..n)
elif nops(l) < n then
add(iter([op(l), q]), q=op(-1, l)..n)
else
mul(binomial(k-1+l[q], l[q]), q=1..n);
fi;
end;
iter([]);
end;
EX :=
proc(n, k)
option remember;
(-1)^n*add(binomial(k-1+m,m)^(2*n)*
mul(1/(binomial(k-1+p,p)-binomial(k-1+m,m)), p=0..m-1)*
mul(1/(binomial(k-1+p,p)-binomial(k-1+m,m)), p=m+1..n),
m=0..n);
end;
No comments:
Post a Comment